Ubezpieczenie kredytu od ryzyka związanego z niskim wkładem własnym kredytobiorcy - Bulik, Magdalena (The low LTV (Loan-to-Value) ratio insurance, 2006)
In the years 1995-2004 in Poland there have been very low borrower incomes. They couldn’t profit by the available conventional financing, especially if the very high house prices and still very high mortgage interests are taken into consideration. But there have some new opportunities appeared. Borrowers who are not able to accumulate enough financial means to take a 25-30% LTV ratio mortgage, can buy the low LTV insurance. The most important aspect of this product is a reduction of a financial deposit that bank requires if taking a mortgage. It means that mortgages can become available for more people who what to have their own house. This product is very general in USA, Canada, England and also it becomes very popular in Poland. The low LTV insurance is not only useful for borrowers, but also it can be profitable for insurers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 23-33